Sustainability of Cooperatives in One City in Negros Occidental - Geroso, Dr. Princess Jeah Marie Sotto; Maguate, Guarin (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to determine Sustainability level of cooperatives in Cadiz City, in terms of its non-financial and financial components. This study is a quantitative and qualitative design of descriptive research. Instruments used were the Cooperative Performance Report Questionnaire and interview questions which were conducted through Focused Group Discussion (FGD) and/or face to face interview. Results revealed that Sustainability of cooperatives in terms of non-financial components when taken as a whole is great. Extent of cooperatives’ sustainability in terms of financial components when taken as a whole is Moderate. No significant relationship between the cooperatives’ non-financial sustainability and financial sustainability when they are taken as a whole and when grouped according to type. No significant difference on extent of cooperative sustainability when assessed in terms of their non-financial components and grouped according to different types of cooperative. No significant difference on extent of cooperatives’ sustainability when assessed in terms of their financial components and grouped according to different types of cooperative. The researcher concluded that cooperatives’ sustainability are much affected by its non-financial components in terms of Human Resource Management, Structure and Social Aspects. In terms of its financial aspects, Institutional Strengths and profitability performance of cooperatives hinder its sustainability.